2012
DOI: 10.4236/cm.2012.33022
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoprotective Diterpenoids Isolated from <i>Andrographis paniculata</i>

Abstract: <i>Andrographis paniculata</i> (Burm.f.) Nees (Acanthaceae), a plant widely used as traditional herbal medicine in many countries, has drawn attention of the researchers in recent years. Its major constituents are diterpenoids and flavonoids. This article reviews the anti-hepatotoxic effects of <i>A. paniculata</i> extract and derivative compounds, such as andrographolide, the major active compound, most studied for its bioactivities. Neoandrographolide shows anti-inflammatory and anti-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 49 publications
0
13
0
Order By: Relevance
“…Apart from the Clerodane-type terpenoid, hypolein B and Crotonpene B have also been reported for Croton hypoleucus by Velazquez et al [11] in the hexane extract of the aerial parts, as well as by Sun et al [24] in the methanol extract of aerial parts of Croton yanhuii. Diterpenoids are well known as compounds with remarkable biological activities, such as anti-tumor, anti-malarial, anti-inflammatory, antimicrobial [25], hepatoprotective [26,27,28,29], and cytotoxic [30]. Some diterpenes may be toxic for humans, resulting in acute or chronic impacts on different tissues and organs.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from the Clerodane-type terpenoid, hypolein B and Crotonpene B have also been reported for Croton hypoleucus by Velazquez et al [11] in the hexane extract of the aerial parts, as well as by Sun et al [24] in the methanol extract of aerial parts of Croton yanhuii. Diterpenoids are well known as compounds with remarkable biological activities, such as anti-tumor, anti-malarial, anti-inflammatory, antimicrobial [25], hepatoprotective [26,27,28,29], and cytotoxic [30]. Some diterpenes may be toxic for humans, resulting in acute or chronic impacts on different tissues and organs.…”
Section: Discussionmentioning
confidence: 99%
“…The herb has been revered for treating infectious diseases and highly regarded as having a preventative effect for many diseases, due to its powerful immune strengthening bene its [31]. Extensive research literatures has revealed that A. paniculata has a broad range of pharmacological activities in different ailments such as anti-analgesic [32], anti-oxidant [33], anti-bio ilm [34], gastro-protective [35], wound healing [36], hepatoprotective [37], anti-ilarial [11], anti-cancer [38], anti-malarial [39] and anti-termites [40]. It has been reported that the prophylactic effect of Andrographis was able to stop the catastrophic effect of the deadly lu virus of 1919 global epidemic from reaching India [41].…”
Section: Azadirachta Indica (Family: Meliaceae)mentioning
confidence: 99%
“…The herb has been revered for treating infectious diseases and highly regarded as having a preventative effect from many diseases, due to its powerful immune strengthening benefits [ 35 ]. Extensive research literature has revealed that A. paniculata has a broad range of pharmacological activities in different ailments such as being antianalgesic [ 36 ], antioxidant [ 37 ], antibiofilm [ 38 ], gastroprotective [ 39 ], wound healer [ 40 ], hepatoprotective [ 41 ], antifilarial [ 14 ], antimicrobial [ 42 , 43 ], anticancer agent [ 44 ], antimalarial [ 45 ], and antitermitic [ 46 ]. It has been reported that the prophylactic effect of Andrographis was its ability to stop the catastrophic effect of the deadly flu virus of 1919 global epidemic from reaching India [ 47 ].…”
Section: Biomedicinal Agents Used Against Filarial Parasitesmentioning
confidence: 99%